Knowledge of sexual health issues among unmarried young people in Nepal - Nicole Stone; Roger Ingham; Padam Simkhada (Asia-Pacific Population Journal, 2003)
Early and universal marriage has traditionally been the norm in Nepalese culture, although the practise of delayed marriage appears to be on the increase. In 1961, nearly 75 per cent of young women aged 15 to 19 years were married; this figure declined to just under 50 per cent by 1991 and to a low of 40 per cent in 2001 (Mehta 1998; Khanal 1999; NDHS 1996 and 2001). This, along with the advent of reducing age at first menarche due to improved nutritional status, has led to an increase in the window of opportunity for premarital sexual activity to occur.